Reduction of nutrient contents by harvesting natural wetland vegetations - Shamsudin, Supiah; Kassim, Mohd. Azraai; Sohaili, Johan (Faculty of Civil Engineering, UTM, 2004)
The effects of harvesting wetlands vegetation on nutrient contents entering Layang reservoir, in Masai Johor were investigated. Total Phosphorus (TP), Total Dissolved Phosphorus (TDP) and Nitrate-N levels at the harvesting site, both upper and bottom layers were lower compared to the control site and the inflowing river. The monthly percentage removals of TP, TDP and Nitrate-N fluctuated noticeably, ranging from 20% to 89%. Percentage removals were also higher after harvesting operation compared to before harvest. The percentage removal is highest when the shoots are young.